Taking Horror as You Find It: From Found Manuscripts to Found Footage Aesthetics - Sawczuk, Tomasz (Text Matters: A Journal of Literature, Theory and Culture, 2020)
An authenticator of the story and a well-tested enhancer of immersion, the trope of the found manuscript has been a persistent presence in Gothic writing since the birth of the genre. The narrative frame offered by purported textual artifacts has always aligned well with the genre’s preoccupation with questions of literary integrity, veracity, authorial originality, ontological anxiety and agency. However, for some time now the application of the found manuscript convention to Gothic fiction has been reduced to a mere token of the genre, failing to gain impact or credibility. A revival of the convention appears to have taken place with the remediation and appropriation of the principally literary trope by the language of film, more specifically, the found footage horror subgenre. The article wishes to survey the common modes and purposes of the found manuscript device (by referring mostly to works of classical Gothic literature, such as The Castle of Otranto, Dracula and Frankenstein) to further utilize Dirk Delabastita’s theories on intersemiotic translation and investigate the gains and losses coming with transfiguring the device into the visual form. Found footage horrors have remained both exceptionally popular with audiences and successful at prolonging the convention by inventing a number of strategies related to performing authenticity. The three films considered for analysis, The Blair Witch Project (1999), Paranormal Activity (2007) and REC (2007), exhibit clear literary provenance, yet they also enhance purporting credibility respectively by rendering visual rawness, appealing to voyeuristic tastes, and exploiting susceptibility to conspiratorial thinking.